Biodegradable Packaging Fillers Reduce Mechanical Damage and Preserve Postharvest Quality of Cherry Tomatoes - Safira Fergiana; Rokhani Hasbullah (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Cherry tomato (Lycopersicum esculentum Mill.) is a perishable commodity due to its delicate texture. Consequently, it necessitates effective postharvest handling. Cherry tomatoes frequently incur mechanical damage during transit due to the voids in the packaging, leading to friction and collisions with the packaging material. This study evaluates the impact of packaging fillers on mechanical damage to tomatoes during transportation and identifies the optimal packaging fillers for cherry tomatoes. This study included plastic fruit crate packaging with dimensions of 38 cm x 26 cm x 12 cm. This study included filler materials consisting of long shredded newsprint and banana leaves and a control group without filler. Transportation simulation was conducted at 3,9 Hz, amplitude 4,2 cm for 90 minutes, equivalent to 108,9 km of transportation. The results showed that packaging with filler significantly reduced fruit damage compared to the control. The highest reduction was observed in the combined filler treatment, which decreased mechanical damage by 62.5% relative to the control. Banana leaf filler also provided good protection, reducing weight loss by 45.8% and maintaining fruit firmness (1.63 kg cm⁻²) compared to control (1.08 kg cm⁻²). However, newsprint filler minimized color change, maintaining the red index 34.15 compared to 41.22 in the control. Overall, the combined filler treatment performed best in preserving postharvest quality. These findings suggest that biodegradable packaging fillers, particularly banana leaves and their combination with newsprint, are effective and environmentally friendly alternatives for extending the shelf life of cherry tomatoes during transportation.